Sphaerodoridium Lutzen 1961 - Plathong, Jintana; Plathong, Sakanan; Capa, María (Zenodo, 2020)
Genus Sphaerodoridium Lützen, 1961 Sphaerodoridium Lützen, 1961; Fauchald, 1974: 270 (in part); Capa et al., 2019: 66. Sphaerodoropsis Hartman & Fauchald, 1971: 69 (in part); Fauchald, 1974: 261 (in part); Borowski, 1994: 23 (in part); Moreira, 2012: 30 (in part); Capa et al., 2014: 17 (in part). Type species . Sphaerodorum claparedii Greeff, 1866. Diagnosis . Body short and ovoid, some forms slender. Prostomial appendages short, spherical or digitiform; median antenna shorter or as long as lateral antennae; antenniform papillae absent or present. Macrotubercles sessile or stalked; smooth, without terminal papilla, arranged in more or less clear longitudinal rows, one transverse row per segment, with at least seven macrotubercles each. Microtubercles absent. Additional papillae over body surface and parapodia. Parapodia with compound chaetae; stout hooks in anterior chaetigers absent (after Capa et al. 2019). : Published as part of Plathong, Jintana, Plathong, Sakanan & Capa, María, 2020, Two new species of Sphaerodoridae (Annelida) from the Gulf of Thailand, pp. 57-75 in Zootaxa 4790 (1) on page 64, DOI: 10.11646/zootaxa.4790.1.3, http://zenodo.org/record/3887857 : {"references": ["Lutzen, J. (1961) Sur une nouvelle espece de Polychete Sphaerodoridium commensalis n. gen., n. spec. (Polychaeta Errantia, famille des Sphaerodoridae), vivant en commensal de Terebellides stroemi Sars. Cahiers de Biologie Marine, 2, 409 - 416.", "Fauchald, K. (1974) Sphaerodoridae (Polychaeta: Errantia) from world-wide areas. Journal of Natural History, 8, 257 - 289. https: // doi. org / 10.1080 / 00222937400770241", "Capa, M., Nygren, A., Parapar, J., Bakken, T., Meissner, K. & Moreira, J. (2019) Systematic re-structure and new species of Sphaerodoridae (Annelida) after morphological revision and molecular phylogenetic analyses of the North East Atlantic fauna. ZooKeys, 845, 1 - 97. https: // doi. org / 10.3897 / zookeys. 845.32428", "Hartman, O. & Fauchald, K. (1971) Deep-water benthic polychaetous annelids off New England to Bermuda and other North Atlantic Areas. Part II. Allan Hancock Monographs in Marine Biology, 6, 1 - 327.", "Borowski, C. (1994) Three new deep-sea species of Sphaerodoridae (Annelida, Polychaeta) from the eastern tropical South Pacific. Zoologica Scripta, 23, 193 - 203. https: // doi. org / 10.1111 / j. 1463 - 6409.1994. tb 00384. x", "Moreira, J. (2012) Familia Sphaerodoridae Malmgren, 1867. In: Parapar, J., Alos, C., Nunez, J., Moreira, J., Lopez, E., Aguirrezabalaga, F., Besteiro, C. & Martinez, A. (Eds.), Annelida Polychaeta III. Fauna Iberica. Vol. 36. Museo Nacional de Ciencias Naturales, CSIC, Madrid, pp. 16 - 43. [in Spanish]", "Capa, M., Bakken, T. & Purschke, G. (2014) Sphaerodoridae Malmgren, 1867. In: Westheide, W. & Purschke, G. (Eds.), Handbook of Zoology. A Natural History of the Phyla of the Animal Kingdom. Annelida: Polychaetes. De Gruyter, Osnabruck. Available from: http: // www. degruyter. com / view / Zoology / bp _ 029147 - 6 - 34 (accessed 18 May 2020)", "Greeff, R. (1866) Ueber die Anneliden-Gattung Sphaerodorum Orst., und einen Reprasentatnen derselben, Sphaerodorum claparedii. Archiv fur Naturgeschichte, 32, 338 - 351. [in German]"]}